Examining Community Resilience to Assist in Sustainable Tourism Development Planning in Dong Van Karst Plateau Geopark, Vietnam. Issue 4 (4th July 2018) - Powell, R. B.; Green, T. F.; Holladay, P. J.; Krafte, K. E.; Duda, M.; Nguyen, M. T.; Spencer, J. H.; Das, Priyam
ABSTRACT: Generally, it is assumed that the well-being of rural communities is linked to their level of resilience. However, despite the importance of community resilience, and its potential to underpin long-term economic development, assessing community perspectives regarding local conditions necessary to support resilience are often ignored during the planning phases of tourism development projects in many areas of the world, especially in countries such as Vietnam, which generally employ top-down planning processes. The purpose of this study is to address this oversight by using household survey techniques to investigate residents' attitudes toward three components of community resilience, environmental, social, and economic resilience, in the context of a tourism development planning process in Dong Van Karst Plateau Geopark in northern Vietnam. The results of the study highlight how understanding community resilience can be used to inform future tourism development efforts including infrastructure development, capacity building, and environment resource management.